Value-based utility adaptive packet schedulers for IPV6-over-IPV4 traffic delay management using diffserv approach - Tiglao, Nestor Michael C. (2005)
Internet Protocol Version 6 (IPv6) is designed to replace Internet Protocol Version 4 (IPv4) and overcome its many limitations. One of these limitations is Quality of Service (QoS). IPv6 provides several levels of QoS while IPv4 provides best-effort delivery only. However, the transition is designed to be a gradual process and transition mechanisms must ensure the smooth coexistence and interoperability of both protocols. The translation and maintenance of end-to-end QoS guarantees between the two protocols must be studied. Our research focuses on the one-way delay performance of a mized IPv4/IPv6 from a Differentiated Services (DiffServ) perspective. The DiffServ architecture defines a small number of service classes and enforces resource allocation on a per-class basis. We setup a network testbed and utilized a combination of mechanisms and strategies including packet marking, packet scheduling, and flow aggregation. We employed the Value-Based Utility (VBU) Model to provide our packet schedulers with the ability to adapt to the network conditions and provide better-then-best-effort network performance. We implemented an adaptive Priority Queuing (PRIQ) and Enhanced Weighted Queuing (EWFQ) scheduler. Our research shows that our adaptive schedulers are able to provide better service compared to their non-adaptive counterparts.